Hubungan Sanitasi Lingkungan Dengan Penyakit Diare Pada Masyarakat Di Desa Tumpapa Indah Kecamatan Balinggi Kabupaten Parigi Moutong Provinsi Sulawesi Tengah - Miswan, Miswan; Ramlah, Siti; Rasyid, Rusman (UNM Environmental Journals, 2018)
Diarrhea is still a public health problem in developing countries such as Indonesia, because it still often arises in the form of outbreaks (Extraordinary Events) and often accompanied by high mortality, especially parts of Eastern Indonesia. This study aims to determine the relationship between the distance of clean water sources, ownership of feces disposal facilities, ownership of waste water disposal facilities and ownership of waste disposal facilities with Diarrhea in the community in Tumpapa Indah Village, Balinggi District, Parigi Moutong District. The type of research used in this study is an analytical survey method with a cross sectional approach which in its implementation both independent variables and dependent variables are carried out simultaneously at the same time. Based on the results of the chi-square test conducted, it shows that the distance of clean water sources has a relationship with diarrheal disease with p-value = 0,000 and latrine ownership also has a relationship with diarrheal disease with a p-value = 0.011. While ownership of the trash has no relationship with diarrheal disease with p-value = 0.318 and ownership of SPAL also has no relationship with diarrheal disease with a p-value = 0.637. Intended for the Balinggi Community Health Center to improve socialization through counseling on good environmental sanitation in order to prevent the occurrence of diarrheal diseases.